Seismic isolation of Advanced LIGO: Review of strategy, instrumentation and performance. (24th August 2015) - Matichard, F; Lantz, B; Mittleman, R; Mason, K; Kissel, J; Abbott, B; Biscans, S; McIver, J; Abbott, R; Abbott, S; Allwine, E; Barnum, S; et al.
Abstract: The new generation of gravitational waves detectors require unprecedented levels of isolation from seismic noise. This article reviews the seismic isolation strategy and instrumentation developed for the Advanced LIGO observatories. It summarizes over a decade of research on active inertial isolation and shows the performance recently achieved at the Advanced LIGO observatories. The paper emphasizes the scientific and technical challenges of this endeavor and how they have been addressed. An overview of the isolation strategy is given. It combines multiple layers of passive and active inertial isolation to provide suitable rejection of seismic noise at all frequencies. A detailed presentation of the three active platforms that have been developed is given. They are the hydraulic pre-isolator, the single-stage internal isolator and the two-stage internal isolator. The architecture, instrumentation, control scheme and isolation results are presented for each of the three systems. Results show that the seismic isolation sub-system meets Advanced LIGO's stringent requirements and robustly supports the operation of the two detectors.